All-Fiber Dual-Wavelength Mode-Locked Laser Using a Bend-Induced-Birefringence Lyot-Filter as Gain-Tilt Equalizer - Yuanjun Zhu; Fulin Xiang; Lei Jin; Sze Yun Set; Shinji Yamashita (IEEE Photonics Journal)
Multi-wavelength fiber lasers have emerged as a promising light source for the application in wavelength division multiplexing communication, terahertz wave generation and optical sensing due to high efficiency and robustness. Lyot-filter emerges as a potential device for multi-wavelength generation application. However, because of the high birefringence of polarization maintaining fiber in Lyot-filter, it is difficult to generate broadband dual-wavelength or multi-wavelength mode-locked fiber laser by using common Lyot-filter. In this paper, for the first time, we propose an idea of using the low birefringence induced by bending the single-mode fiber to form a Lyot-filter for dual-wavelength mode-locked fiber laser generation. The dual-wavelength output centers at 1532 and 1556 nm and it may simplify the set-up for dual-wavelength mode-locked laser.